Relationship marketing as a modern marketing concept in the Republic of Moldova - Dilan, Nelly (CEP USM, 2024)
The article aims to analyze the application of relationship marketing as a modern marketing concept in the Republic of Moldova, highlighting its significance in fostering customer loyalty and competitive advantage for Moldovan companies.
Keywords: Relationship marketing; customer loyalty; competitive advantage; Republic of Moldova; marketing strategy; customer retention